2021
DOI: 10.1177/00048674211009620
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of metabolic side-effects in children and adolescents prescribed antipsychotic medication: A systematic review

Abstract: Objectives: Prescribing antipsychotic medications to children and adolescents with severe mental and developmental disorders is common; however, there is a lack of consensus on appropriate metabolic monitoring for this population. This review systematically evaluates studies examining metabolic monitoring of children and adolescents prescribed antipsychotic medication to understand the clinical practice of metabolic monitoring and identify opportunities to improve the safety of antipsychotic prescribing in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Previous literature showed that the first-line antidepressants may not achieve satisfactory effect in 60% of adolescents with MDD (14). Some limitations associated with interventions for acute onset of adolescents with mental disorders include slow effectiveness, lack of well-tolerated and effective pharmaceuticals, and limited pharmaceutical therapeutic options (15,16). Besides that, there are hidden safety risks in antidepressant medication, such as selective serotonin reuptake inhibitors (SSRIs) could increase the risk of suicidality and self-injury in youth (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature showed that the first-line antidepressants may not achieve satisfactory effect in 60% of adolescents with MDD (14). Some limitations associated with interventions for acute onset of adolescents with mental disorders include slow effectiveness, lack of well-tolerated and effective pharmaceuticals, and limited pharmaceutical therapeutic options (15,16). Besides that, there are hidden safety risks in antidepressant medication, such as selective serotonin reuptake inhibitors (SSRIs) could increase the risk of suicidality and self-injury in youth (17,18).…”
Section: Introductionmentioning
confidence: 99%